Application of remote sensing technology integrated geographic information system (GIS) mapping of land use changes of Nam Dinh Province - Hạnh, Lê Đức; Lan, Vũ Thị Thu; Sơn, Hoàng Thanh; Long, Vũ Phan (Vietnam Journal of Earth Sciences, 2014)
This paper presents the results of remote sensing technology application combined with geographic information systems (GIS) in mapping land use changes in Nam Dinh province at the scale of 1:25.000 from 2003 to 2011. On the basis of SPOT 5 remote sensing image interpretation which has been merged with the panchromatic channel (Pan), refering to current land use map in 2000, 2005, 2010 of the Department of Natural Resources and Environment in Nam Dinh province, we has been conducted current land use maps in 2003, 2008 and 2010. Connecting status maps produced land use changing maps for each short period, building up the matrix of changes in land use. Research results show that the land use changes in Nam Dinh province has been varying strongly from 2003 to 2011. This is caused by the socio-economic activities, that's process of urbanization, modernization in the central southern Red River delta.Besides, the other natural activities such as erosion, accretion in the coastal of Nam Dinh province, where 3 large estuaries of Red River system are operating strongly, also took place very significantly.